Study on Parameter Optimization and Mechanism of Rigid-Flexible Coupling Underground Engineering Structure of Steel Panel and Polymer - Dengping Hu; Chunyan Wang; Zhe Luo; Xuanxuan Chu (Advances in Civil Engineering)
Polymer grouting is carried out between the steel panel and surrounding soil in underground engineering, and the polymer material consists of isocyanates and polyols. The isocyanate/polyol composite slurry expands rapidly due to chemical reaction and solidifies immediately. Then, a dense impermeable polymer layer is formed after rapid expansion of isocyanate and polyol, which is widely used for ground reinforcement and foundation remediation. Thus, a steel panel-polymer composite structure is developed. Mechanical properties of the steel panel-polymer structure are studied. The results show that the steel panel-polymer structure exhibited excellent mechanical properties. The steel panel and polymer layer should be designed above 3 mm and 10 mm in thickness, respectively. The steel panel showed superior mechanical properties to those of polymer layers. Considering good rigidity of the steel panel and good flexibility of the polymer layer, the steel panel and polymer layer presented perfect interfacial contact. It is concluded that the mechanical properties of the whole structure were increasingly enhanced with the increase of the steel panel thickness and the structural flexibility increased with the thickness of the polymer layer. Besides, the combination of the steel panel and polymer layer could also improve the mechanical properties of this coupling structure. This study provided an initial attempt for investigating the feasibility of applying polyurethane foam to steel panels in underground engineering. The stress analysis along the grouting direction inside the prefabricated wall was conducted. It may lay the foundation for further application of polymer grouting in underground engineering.